Detecting significant decreasing trends of land surface soil moisture in eastern China during the past three decades (1979–2010). Issue 10 (17th May 2016) - Chen, Xiuzhi; Su, Yongxian; Liao, Jishan; Shang, Jiali; Dong, Taifeng; Wang, Chongyang; Liu, Wei; Zhou, Guoyi; Liu, Liyang
Abstract: Understanding the historical trends and driving mechanism of China's soil moisture change is an important step in combating climate change. Using the time series satellite‐derived Essential Climate Variable Soil Moisture (ECV_SM) product, we detected a significant decrease trend in land surface soil moisture in eastern China over a 32 year period (1979–2010). Theoretical sensitivity analysis suggested that soil moisture is regulated collectively by precipitation ( P ), potential evapotranspiration (PET), land surface conditions such as land cover/use changes, landscape features, irrigation and urban expansion, ( m ), and the water balance between input and output water supplies O (the input water supplies minus the output). The change in spatial pattern and temporal trend of P /PET is highly consistent with the corresponding change in soil moisture. The magnitude of soil moisture variation is also well correlated with that of P /PET ( R 2  = 0.43; p  < 0.001). Therefore, P /PET is believed to be the dominant factor in determining the temporal trends of soil moisture change. Among the 29 drainage basins with significant decreasing trend of soil moisture change, the areas of forest cover increased by 36.08% and the average topographic slope was twice steeper than that of other regions. Therefore, besides the climate factor ( P /PET variable), land surface conditions (such as land cover changes and topographic) also played important roles in regulating the trend of regional soil moisture change. Key Points: Low soil moisture cluster phenomenon has occurred in northwestern China Significant decrease trend of soil moisture was detected in eastern China P /PET, land cover/use, and landscape are responsible for the soil moisture trends